THE LEGAL POSITIN OF ADJUSTMENT OF THE DEED MADE WITHOUT INVOLVING ONE OF THE FOUNDING PARTIES OF THE FOUNDATION (Case Study of Decision Number 1/ Pdt. G/2020/PN. Bau) - selvianah, shely; Susetyo, Heru (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The Articles of Association of the Foundation in its rules can be changed except regarding the purpose and objectives of the foundation. Amendments to the foundation’s articles of association are carried out with the application submission procedures. They are regulated in Article 15 to Article 23 of Law Number 16 of 2001 concerning foundations. The foundation’s founder is one of the parties that plays an important role in every action. Moreover, Article 28 paragraph 4 of the Foundation Law states that if the Foundation for any reason no longer has a Trustee, no later than within 30 (thirty) days from the date of vacancy, the Management members and Supervisory members must hold a joint meeting to appoint a Trustee by taking into account the provisions referred to in paragraph (3). Such an event requires the role of a Notary to make a Deed of Minutes of the Meeting to record the changes in the deed to replace the management in the deed of amendment or adjustment of the foundation.